The Effect of Ascorbic Acid and Sodium Stearoyl-2 Lactylate on Frozen Dough Stability; Dondurulmuş Hamur Stabilitesine Askorbik Asit Ve Sodyum Stearol-2-laktilat'm Etkisi - Koca, A.F.; Anil, M. (TÜBİTAK, 1999)
The present study consitst of two parts of research. In the first part, the effect of varying closes of ascorbic acid (AA-0, 75 and 125 ppm) and sodium stearoyl -2- lactylate (SSL-0, 0.5 %) used in frozen doughs on bread characteristics after 2 months storage period. In the second part the effect AA alone and AA+SSL after three cycles of freeze-thaw on proof time and bread characteristics was investigated. The results are presented below statisticaly (p<0.05, p<0.01). Spesific volume was significantly higher in the AA group than control group. Bread quality was found high at the dose of 125 ppm AA. SSL concentration of 0.5% significantly improved specific volume and bread quality. The highest bread quality was observed with the use of 125 ppm AA+0.5% SSL combination. In the case of the freeze-thaw cyle numbers increased; proof time extended and bread quality decreased. To prevent these effects, using 125 ppm AA+0.5 SSL combination gave the best results according to 125 ppm AA alone.
Dondurulmuş Hamur Stabilitesine Askorbik Asit ve Sodyum Stearol -2-Laktilat'ın Etkisi